Kapasitas Remaja Akhir dalam Menghadapi Bencana Banjir di Kelurahan Bidara Cina, Kecamatan Jatinegara, Kota Jakarta Timur - Muhammad Farhan Damar Pamungkas; Rayuna Handawati; Sony Nugratama Hijrawadi (Geography Education Study Program, Universitas Kanjuruhan Malang, 2024)
This study aims to determine the capacity of late adolescents in facing flood disasters in Bidara Cina Village, East Jakarta City. People in this area consider floods as normal so they need to increase awareness of the dangers of floods and how to overcome them. The method in this study is quantitative descriptive using survey approach techniques. The population in this study was 3,182 people. While the research samples amounted to each of the four RW samples, namely RW 03 totaling 17 samples, RW 05 totaling 13 samples, RW 06 totaling 11 samples, RW 07 totaling 36 samples, and RW 011 totaling 23 samples. The total sample in the study in Bidara Cina Village, East Jakarta City amounted to 100 respondents. This study uses three aspects used to measure the capacity of late adolescents, namely aspects of knowledge, aspects of action plans and aspects of local wisdom. Each aspect has a score, in the knowledge aspect it has a fairly good score of 65.8%, the action plan aspect has a score of 50.1%, and the local wisdom aspect has a score of 52.2%. After calculations were made on the results of the study, it was found that the capacity of late adolescents in dealing with flood disasters had a percentage of 57.3% included in the medium category. Therefore, there is still a need for socialization and debriefing for late adolescents there to increase the capacity of late adolescents and reduce the impact when facing floods.